Tailoring psychiatric treatment using genetic information: pharmacogenetic prediction of treatment response - Arranz, Maria (Henry Stewart Talks, 2007)
Pharmacological treatment in psychiatry, Causes of treatment variability, Contribution of genetic variants of the CYP enzymes to drug metabolism, Influence of genetic variance on drug treatment, Influence of genetic variance on treatment-induced side-effects, Prediction tests for psychotropic drug response
Updated at 2014/12/02